دور وسائل الإعــلام في تنمية السياحة الصحراوية- ولاية الوادي أنموذجا - بوترعه, بلال; بن عمار, أشواق (جامعة الوادي - University of Eloued, 2021)
إزاء التعاظم المستمر لقطاع السياحة فإن وجود إستراتيجية علمية مبنية على أسس تسويقية صحيحة تمثل نقطة البداية لانطلاق ونجاح أي جهد سياحي هادف لاجتذاب المزيد من السياح والمزيد من الإرادات وهذه المسؤولية تلقى على عاتق الأخصائيين في مجال التسويق الإعلام والإرشاد السياحي. فعلى المستوى المحلي تمثل الصحراء في الجزائر النفط الحقيقي والدائم الذي يقدم للخزينة الجزائرية مليارات الدولارات سنويا، وهذا إذا ما تم الاهتمام بهذا القطاع من الناحيتين الإعلامية والتسويقية، ذلك لأن المواقع الصحراوية والتاريخية المتواجدة بولاية الوادي "واد سوف" وكذا المواقع السياحية المنتشرة عبر كامل التراب الوطني لا يمكن التقليل والتغاضي عن أهميتها الإنسانية والحضارية والاقتصادية، أذا ما لقيت الاهتمام الكافي والرعاية اللازمة في الجانب التنظيمي والتمويلي والإعلامي، هذا الأخير الذي يعتبر من أهم الآليات التي تعمل على تنمية القطاع السياحي. Abstract: In light of the continuous growth of the tourism sector, the existence of a scientific strategy based on correct marketing foundations represents the starting point for the launch and success of any targeted tourism effort to attract more tourists and more wills, and this responsibility rests with specialists in the field of marketing, information and tourism guidance. At the local level, the Sahara in Algeria represents the real and permanent oil that provides the Algerian treasury billions of dollars annually, and this is if attention is paid to this sector in terms of media and marketing, because the desert and historical sites located in the wilaya of Oued Souf, as well as the tourist sites spread across the entire national territory. Its human, civilization and economic importance cannot be underestimated or overlooked, if it receives sufficient attention and the necessary care in the organizational, financing and media side, the latter which is considered one of the most important mechanisms that work to develop the tourism sector.
The role of the mass media in developing desert tourism - Wilaya d'El Oued as a model
مقال
Keywords: السياحة، الإعلام السياحي، الاتصال السياحي، السياحة الصحراوية; Tourism , Tourist Information , Tourist Communication , Saharan Tourist